STUDI KELAYAKAN MATERIAL GUNUNG DAERAH ALIRAN SUNGAI ARAH MALANG-KOTA BATU DALAM PENGGUNAANNYA SEBAGAI SALAH SATU MATERIAL BETON - Armin Naibaho; Agus Sugiarto; Purnama Dewi (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2020)
Abstract The use of the mountain seal used as a building block for concrete should be considered, based on current usage apart from being a light construction material for housing, mountain materials from these two places are used as the main aggregate material for building construction, water structures (dams), roads. and bridges located in the surrounding Malang-Kota Batu area To determine the size of the aggregate, the coarse aggregate is sieved using a vibrating sieve, while the fine aggregate is sieved by a hydraulic sieve. In the screening process, about 70% of the filtered must pass so that high efficiency and capacity can be achieved. The compressive strength test results obtained the average compressive strength value at 28 days of concrete for concrete with fine aggregate sand zone III and coarse aggregate (gravel) in the Batu City area is equivalent to 35.65 MPa. The results of the split tensile strength test showed that the average split strength value at the age of 28 days for concrete with fine aggregate sand zone III and coarse aggregate (gravel) in the Kota Batu area is equivalent to 2.51 MPa. The compressive strength value for normal concrete is 35.65 MPa, it should produce split tensile strength = 4.179 MPa according to the provisions of SNI T-15-1991-03 Article 3.2.5 (fr = 0.70√fc '). Even though the split tensile strength value obtained in the laboratory is only 2.51 MPa, this means that the quality of materials (sand and broken stone) from Batu City is not suitable for use as building materials. Because the number 2.51 MPa is relatively much smaller than the value of 4.179 MPa, it is only one of the factors outlined in the SNI T-15-1991-03 article 3.2.5. Keywords: Mountain Material, Concrete, Concrete Compressive Strength Test, Concrete Tensile Strength Test